OPTIMALISASI PERAN MAHASISWA PBSI DALAM PKM MELALUI SOSIALISASI DAN COACHING - Lewier, Mariana; Supriyono, Areni Yulitawati; Triyana, Eka (Universitas Pattimura, 2025)
The low participation of students in the Student Creativity Program (PKM) is due to a lack of understanding and experience in proposal writing, even though PKM is a crucial platform for developing students' academic and non-academic potential. This community service program was initiated to enhance the capacity of students from the Indonesian Language and Literature Education Study Program (PBSI) at Universitas Pattimura to compete at the national PKM level. The method involved socialization, technical training, intensive mentoring, and proposal evaluation. Evaluation was based on active student participation in each stage and the quality of proposals produced, with success indicators including the number of groups formed, improved conceptual understanding, and proposal readiness according to national standards. The results showed a 100% increase in participation—from zero to four student groups submitting proposals, consisting of one PKM-AI group and three PKM-RSH groups. The quality of proposals also improved in terms of structure, originality, and feasibility. Sustainability strategies included establishing the PBSI PKM Community and involving alumni as active mentors. This program demonstrated that a structured training and mentoring approach can significantly enhance student preparedness in PKM competitions